1986
DOI: 10.1017/s0021859600069744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of density and nitrogen fertilizer on the growth and yield of maize (Zea maysL.) in Nigeria

Abstract: FARZ 27, a high-yield maize variety, was grown in 1984 and 1985 over a wide range of density treatments (1-9-11-1 plants/m 2 ) and with four rates of nitrogen application (0, 75, 100 and 150 kg N/ha) in Ibadan. south-western Nigeria.There was no significant density or fertilizer effect on morphological characters of number of leaves per plant, height or stem diameter. For total dry-matter yield, the highest density of planting gave the highest yield although less dry matter was obtained in the 1985 experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…These results are in agreement with those obtained by several investigators such as Lucas (1986) and El-Bana & Gomaa (2000). Table 6 indicate that maize yields and its components were significantly influenced by maize orientation in the intercrop in both seasons, except, ear diameter, differences failed to reach the 5% level in both seasons.…”
Section: Maize Effect Of Intercropping Patternssupporting
confidence: 94%
“…These results are in agreement with those obtained by several investigators such as Lucas (1986) and El-Bana & Gomaa (2000). Table 6 indicate that maize yields and its components were significantly influenced by maize orientation in the intercrop in both seasons, except, ear diameter, differences failed to reach the 5% level in both seasons.…”
Section: Maize Effect Of Intercropping Patternssupporting
confidence: 94%
“…These densities are 53,333, 66,666, and 79,999 plants-ha 1 . The lowest plant density is the current recommended plant density for maize hybrids in Nigeria (Ebong and Wahua, 1991), while the highest plant density is a typical plant density under high fertilizer treatment levels (Lucas, 1986). The subplots consisted of three different times of N application: (i) the entire N applied at two weeks after planting (Table 1), (ii) split application of N at two equal doses, half at planting and the other half at 4WAP (Table 2), and (iii) application of N at two equal doses half at planting and the other half at 50% flowering (Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…This recommendation is likely to be based on earlier studies where optimum density of 53,000-66,000 plants/ha gave optimum grain yield (Lucas, 1981). However, using high yielding FARZ 27 genotype, optimum yield at population density of 88,000 plant/ha was reported (Lucas, 1986). The density of 80,000 plants/ha was found optimal for hybrid maize varieties grown in Kaduna that is, Northern Guinea savanna zone of Nigeria and 53,333 plants/ha for Ikenne and Mokwa representing the forest and southern Guinea savanna zones respectively (Akintoye et al, 1997).…”
Section: Density Of Plantingmentioning
confidence: 99%
“…Common nitrogen recommendation for old NS series in Nigeria is 75 kgN/ha (Jones, 1973). Lucas (1986) recommended 150 kgN/ha for FARZ series based on profitability, although the yield of maize at 75 kgN/ha was not significantly different from the yield at 150 kgN/ha, while Akintoye et al (1999) reported responses up to 70, 140 and 210 kg N/ha for maize grown in Ikenne, Mokwa and Kaduna respectively, using different maize genotypes.…”
Section: Fertilizer Requirements Of Maizementioning
confidence: 99%